2022
DOI: 10.1021/acsanm.2c04747
|View full text |Cite
|
Sign up to set email alerts
|

Fe3O4 Nanoparticles Embedded in Pectin–Doxorubicin Composites as pH-Responsive Nanoplatforms for Tumor Diagnosis and Therapy by T1-Weighted Magnetic Imaging

Abstract: Multifunctional nanomaterials with diagnostic and therapeutic capabilities offer promising customized nanomedicines for cancers. However, achieving good execution of these functions in vivo employing a single nanoframework remains challenging, and only a few of these magnetic nanocarriers have been validated for clinical use. In this study, based on biocompatibility and remarkable multifunctionalities, we describe a novel approach to synthesize small Fe 3 O 4 nanoparticles conjugated with natural polysaccharid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Surveys such as that conducted by Yao-Jiang Ye et al [152] have shown that hybrid NPs co-loaded with copper sulfide (CuS) NPs and glucose oxidase (GOD) (CuS@GOD NPs) have in vivo feasibility for use in multiparametric MRI, including intravoxel incoherent motion diffusion-weighted imaging (IVIM-DWI) and R 2 * mapping for cancer detection and treatment response. It has been demonstrated that [153] Fe 3 O 4 @PD NPs result in T 1 MRI darkening and brightening contrast enhancement at tumor sites, and the relative signal-to-noise ratio of the tumor can be used for distinguishing normal and tumor tissues.…”
Section: Nanoparticles In Mrimentioning
confidence: 99%
See 1 more Smart Citation
“…Surveys such as that conducted by Yao-Jiang Ye et al [152] have shown that hybrid NPs co-loaded with copper sulfide (CuS) NPs and glucose oxidase (GOD) (CuS@GOD NPs) have in vivo feasibility for use in multiparametric MRI, including intravoxel incoherent motion diffusion-weighted imaging (IVIM-DWI) and R 2 * mapping for cancer detection and treatment response. It has been demonstrated that [153] Fe 3 O 4 @PD NPs result in T 1 MRI darkening and brightening contrast enhancement at tumor sites, and the relative signal-to-noise ratio of the tumor can be used for distinguishing normal and tumor tissues.…”
Section: Nanoparticles In Mrimentioning
confidence: 99%
“…Tao et al [153] Small Fe 3 O 4 NPs MRI ✓ ✓ Fe 3 O 4 @PD-based system has the potential to be a multifunctional nanodrug delivery system and a smart theragnostic platform for cancer detection and treatment.…”
Section: ✓ ✓mentioning
confidence: 99%
“…Surveys such as that conducted by Yao-Jiang Ye et al [150] have shown that, the hybrid NPs co-loading with copper sulfide (CuS) NPs and glucose oxidase (GOD) (CuS@GOD NPs) have in vivo feasibility of using for multiparametric MRI including intravoxel incoherent motion diffusion-weighted imaging (IVIM-DWI) and R2* mapping for cancer detection and treatment response. It has been demonstrated that [151] Fe3O4@PD NPs results T1 MRI darkening to brightening contrast enhancement at tumor sites, and the relative signal-to-noise ratio of the tumor for distinguishing the normal and tumor tissues.…”
Section: Nanoparticles In Mrimentioning
confidence: 99%
“…Tao et al [151] small Fe3O4 NPs MRI ✓ ✓ Fe3O4@PD-based system has the potential to be a multifunctional nanodrug delivery system, and as a smart theragnostic platform for cancer detection and treatment.…”
Section: ✓ ✓mentioning
confidence: 99%